Synergic Effect of HNT/oMMT Bi-filler System for the Mechanical Enhancement of PLA/PBAT Film - Ko, Eunjoo; Kim, Taeho; Ahn, Jungbin; Park, Sanghyun; Pak, Sewon; Kim, Minhyung; Kim, Hyungsup (Fibers and polymers, 2021)
Mechanically enhanced Poly(lactic acid) (PLA)/Polybutylene adipate terephthalate (PBAT)/nano filler composite film was prepared by melt blending. Halloysite nanotubes (HNTs) and modified montmorillonites (oMMTs) were used as filler, separately or simultaneously. The improvement of the miscibility between PLA and PBAT by the help of oMMTs was observed using cross-sectional SEM images and rheological analysis. The mechanical properties of the composite films were studied with DMA and UTM. The bi-fillered composite film displayed the improvement in the modulus and the tensile strength by the interconnected network of HNTs and oMMTs. The PLA/PBAT/bi-filler film shows a prospective vision for the biodegradable packaging area.